The relationship between contingent factors that influence the environmental management accounting and environmental performance among manufacturing companies in Klang Valley, Malaysia - Ong, Tze San; Teh, Boon Heng; Selley, Selvi; Magsi, Hussain Bakhsh (Faculty of Economics and Management, Universiti Putra Malaysia, 2018)
Environmental issues are attracting increasing attention in Malaysia with the tremendous increase in waste generation; the cost of production and waste treatment is getting expensive. Data from the Malaysian Environmental Department shows that 80% of the waste is generated by the manufacturing industry. Firms are constantly requested to change their business practices to incorporate environmental activities. It also indicates that future natural resources are being squandered as waste due to less exposure to environmental management accounting, which results in unproductivity, overproduction, increase in total delivery cost, or inefficiency in manufacturing plant. This research exploits the quantitative research methodology to understand the relationship between contingent factors, which are uncertainty in the environment, organizational size, environmental strategy, regulatory pressure, and top management commitment that influence environmental management accounting and environmental performance among manufacturing companies in Klang Valley, Selangor. The survey was conducted on manufacturing companies located in Klang Valley, based on the 2,400 companies registered in the Federal Malaysian Manufacturer (FMM) database. 600 questionnaires were sent out to manufacturing companies and the finding highlights that the uncertainty in the environment, regulatory pressure, and top management commitment significantly affect environmental performance.